PERHITUNGAN VOLUME BATUAN MENGGUNAKAN SOFTWARE AUTOCAD CIVIL 3D DENGAN METODE RULE OF GRADUAL CHANGE DAN RULE OF NEAREST POINT - Jarwanto, Jarwanto; Arie Noor Rakhman,; Himawan Rico Sanjaya, (Nusantara Hasana Journal, 2025)
The research was conducted in an area located in Segoroyoso, Kapanewon Pleret, Bantul Regency, Yogyakarta Special Region Province. The enclosing rocks are part of the Semilir Formation in the form of tuff interspersed with lapilli. The rock located on this cliff will be cut with a length of 83 meters and a height of 36 meters with the aim of making a flat horizontal plane with an elevation of 50 meters above sea level which will then be made into building construction for the purposes of erecting boarding school buildings. The calculation of rock volume is based on Autocad Civil 3D software with the emphasis on 2 calculation methods, namely calculations using the Rule of Gradual Change and getting a volume of 106,714 m3 and according to the Rule of Nearest Point method getting a volume of 106,495 m3. There is a difference in the calculation results but the difference is not far adrift.